A preliminary service evaluation of a personality disorder case management service. (25th February 2019) - Graham, Simon; Sullivan, Kathia; Briggs, Laura; Goodall, Mark; Iraci Capucinello, Rosella
Abstract: Aims: The aim of this study is to assess the impact of establishing a specialized community personality disorder team on out of area placements, local hospital admissions and out of hours crisis contacts for service users with borderline personality disorder. Method: This is a before–after interim evaluation of a new service. We tested, through a paired t ‐test, whether the intervention generated statistically significant differences over a range of measures of service usage, including out of area placements, local hospital admissions and out of hours crisis contacts. Data from 12 months after the intervention started were compared with the previous 12 months of routine care, to determine the effect on crisis contacts, days in hospital and those returning from/or sent out of area for care. Finally, we have assessed the likelihood to generate cost savings. Results: All service users in out of area placements were repatriated to live in the community locally (100%), and there was a statistically significant decrease in inpatient admissions (80%). This was counterbalanced by a smaller but statistically significant increase in out of hours community crisis contacts (30%), although these reduced over time. Conclusion: Reorganizing local care pathways can lead to less out of area placements and less hospital admissions. © 2019 John Wiley & Sons, Ltd.